Estimating the State-of-Charge of All-Vanadium Redox Flow Battery using a Divided, Open-circuit Potentiometric Cell - Mohd Rusllim, Mohamed; Hamzah, Ahmad; Mazrul Nizam, Abu Seman (KTU, 2013)
In this paper, mathematical modelling of oxidation-reduction redox potential for estimating the state-ofcharge of V-RFB is presented. The estimation is based on the Nernst equation, a mass balance, Faraday’s law of electrolysis, and 1st order kinetic equation. The 25-100 cm2 laboratories, unit cell V-RFB is chosen as a model reaction for electrolyte redox potential measurement. Preliminary experiment is carried out using a 100 cm2 laboratory unit but the estimated value produced is inaccurate. An alternative design of 25 cm2 laboratory, unit cell V-RFB using a divided, open-circuit potentiometric cell is used. The redox potential of V(III)/V(II) and V(IV)/V(V) is measured through combined Hg/Hg2SO4 reference electrode and carbon rod working electrode. The differences between the experimental and estimated values are highlighted.